Design of Orbit Controls for a Multiple CubeSat Mission Using Drift Rate Modulation - Youngbum Song (MDPI AG, 2021)
For the low-cost improvement of laser communication, which is critical for various applications such as surveillance systems, a study was conducted on relative distance control based on orbital drift rate modulations for multiple CubeSats during formation flying. The VISION mission covered in this paper comprises two CubeSats to demonstrate laser communication technology in space. During the mission, the deputy CubeSat changes the relative distance to execute mission objectives within various scenarios. Impulsive controls decrease, maintain, and increase the relative distance between the CubeSats by changing the orbital drift rates. The simulation results indicated that the desired orbital operation can be conducted within a given <semantics><mstyle mathvariant="bold" mathsize="normal">Δ</mstyle>V</semantics> budget. In addition, the errors in the orbit determination, thrust maneuvers, and time synchronization were analyzed to satisfy the mission requirements. The mass-to-area ratio should be matched to adjust the relative distance between satellites with different properties by drift rate modulation. The proposed orbit control method appropriately operated the VISION mission by adjusting the drift rate modulation. The results of this study serve as a basis for the development of complex orbit control simulations and detailed designs that reflect the characteristics of the thrust module and operational aspects.